(3ebGdI GdEScfOQ GdEaQhOjSi aj Gdgjhdi hCfgG eaYhdIs - (3GdEScfOQ GdEaQhOjSis
(3ChdgG (B:s
(3bGd GdEScfOQ (B: (3hEf cd cGFf HGdbhI EfeG jchf HGdaYd ef BNQ gh HGdaYd s
(3BNQgG (B:s
(3hCfgG bGHdI ddUhQ HdG MQcI hdG ESJMGdI JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/16) s
Keywords: (3GdadSaI hGdefWbs